The relationship between the exercise capacity and somatotype components, body composition, and quadriceps strength in individuals with coronary artery disease - Gültekin, Melike; Yeginoǧlu, Gülay; Bingöl, Hasan (National Scientific Medical Center, 2021)
Aim: The purpose of this cross-sectional study was to explore a possible relationship between exercise capacity and somatotype components, body composition, and quadriceps strength in individuals with coroner artery disease (CAD) Material and methods: A convenient sample size of 60 participants between the ages of 45 and 60 years (mean age 56.6±4.7; 12 females [mean age 57.7±3.01], 48 males [mean age; 56.3±5.1] was established f rom patients referred to the Department of the Cardiopulmonary Rehabilitation. The exercise was assessed using graded symptom-limited exercise testing while Participants' body composition was detected via Bioelectrical impedance analysis (BIA) technique by using TANITA SC-330 (TANITA, Tokyo, Japan). Finally, quadriceps femoris muscles testing was conducted with Dr. Robert W. Lovett’s manual muscle testing method. Results: In the whole sample, exercise capacity was found to be negatively and weakly correlated with the endomorph component (r=-0.39), whereas a slight and positive correlation was observed between the ectomorph component and exercise capacity (r=0.28). However, the correlations revealed between exercise capacity and somatotype components differentiated with gender-based analysis. A moderate and weak correlation was found out between exercise capacity and fat mass (FM) in the whole group and the male individuals (r1=-0.45 and r2=-0.34), respectively; in contrast, there was not a meaningful correlation between the same variables in the female individuals (r=-0.002). Exercise capacity had slight and negative relationships with f ree-fat mass variable (FFM) in both gender (r1=-0.28 and r2=-0.29), while small to moderate relationship with fat-mass variable (FM) in the male gender (r1=-0.34). Body composition elements, including FM, FFM and BMI, together explained a % 24 of variance in exercise capacity, while somatotype components together explained a % 16 of variance in the exercise capacity. Finally, quadriceps femoris strength was found to be the best predictor of exercise capacity of a patient with CAD (R2=0.44 or % 44) Conclusion: Our results suggest that exercise capacity in individuals with CAD is directly associated with somatotype components, anthropometry/ body composition elements, and quadriceps strength. © 2025 Elsevier B.V., All rights reserved.
Keywords: Aerobic Capacity; Body Mass Index; Coronary Artery Disease; Fat Mass Index; Peak Metabolic Equivalent